Conditions for tourist travels to the Warmian-Masurian Voivodeship during the COVID-19 pandemic - Bogusławska, Małgorzata; Podhorodecka, Katarzyna (Sport and Tourism Central European Journal, 2023)
The aim of this article is to show what was the level of tourist travels and tourism development in the Warmian-Masurian voivodeship during the COVID-19 pandemic times. The article presents the main factors that influenced the development tourist arrivals in this region. The methods used were observations, analysis of literature, analysis of strategic documents and analysis of data collected by a questionnaire. The article analyses the conditions of the area enhancing the development of tourism, including climate, road and rail infrastructure and tourist routes. In addition, tourist attractions in the province were highlighted and reference was made to the existing tourist infrastructure–accommodation and catering facilities. A questionnaire was also carried out pertaining to tourists’ opinions about travels during the COVID-19 pandemic time.